PENINGKATAN MENULIS PENGALAMAN PRIBADI DENGAN MENGGUNAKAN MODEL INVESTIGASI KELOMPOK SISWA KELAS VIII MTS AL-KHAIRAAT GURUAPING OBA UTARA - Justam Wahab (EDUKASI, 2021)
The research was conducted with the objectives of (1) to find out the results of using the group investigation model in learning to write personal experiences for class VIII MTs students. Al-Khairaat Guruaping oba north. (2) To find out the improvement of personal experience writing skills by using the group investigation model of class VIII MTs students. Al-Khairaat Guraping oba north. The method used in this research is quantitative descriptive. The population in this study were 70 students of class VIII MTs. Alkhairaat Guruaping oba north. While the sample in this study was 30 students by 50%. Based on the results of the analysis and conclusions, it can be seen that (1) the observations of teachers in the field of Indonesian language studies have carried out the teaching and learning process well in accordance with the implementation of the curriculum and the use of learning tools in the form of syllabus and lesson plans in writing personal experiences; (2) teacher interviews in the field of Indonesian language studies have taught students with personal experiential writing learning materials and teachers have used cooperative investigative type models to improve student learning outcomes; (3) pretest (pretest) students who get very good qualifications (SB) as many as 6 by 20%, students who get good qualifications (B) as many as 8 by 26%, students who get quite good qualifications (CB) as many as 8 by 26 %, students who received poor qualifications (KB) were 5 by 16. Not yet achieved improvement; (4) final test (protest) students who get very good qualifications (SB) are 14 by 46%, students who get good qualifications (B) are 7 by 23%, students who get quite good qualifications (CB) are 9 by 30 %, students who get poor qualifications (KB) as many as 0 students by 0% achieve an increase.